Conservation of the glycogen metabolism pathway underlines a pivotal function of storage polysaccharides in Chlamydiae - Matthieu Colpaert; Derifa Kadouche; Mathieu Ducatez; Trestan Pillonel; Carole Kebbi-Beghdadi; Ugo Cenci; Binquan Huang; Malika Chabi; Emmanuel Maes; Bernadette Coddeville; Loïc Couderc; Hélène Touzet; et al. (Communications Biology, 2021)
Matthieu Colpaert et al. use biochemical and comparative genomic analyses and identify a trehalose-dependent glycogen synthesis pathway in W. chondrophila and E. lausannensis. These results suggest that the glycogen metabolism pathway is conserved in all Chlamydiales species.